Stiffness After Total Knee Replacement - Andrade Costa, Jorge; Serviço de MFR, Hospital Curry Cabral, Centro Hospitalar Lisboa Central, Lisboa, Portugal (2016)
The goals of total knee arthroplasty are to minimize knee pain, promote articular stability during gait and maximize the range of motion. The prevalence of knee stiffness after arthroplasty can reach 25%. The scientific community points out, as main risk factors for its appearance, a smaller preoperative range of motion, the lack of collaboration of the patient in a rehabilitation program, patella ínfera and the use of coumarinic anticoagulation. The improvement of knee range of motion rarely occurs after six months of arthroplasty, even under an appropriate rehabilitation program. In case of postoperative stiffness, the most effective option for current gain of range includes joint manipulation under anesthesia. Arthroscopic or open arthrolysis has modest results in the gain of range of motion as well as revision arthroplasty. However, the latter proves to be effective in individual cases of stiffness with flexion contracture.